How to Prevent Stroke in Hypertension Patients? - Arum Dwi Ningsih; Rizky Meuthia Pratiwi; Lutfi Wahyuni; Binarti Dwi Wahyuningsih (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Stroke is a disease that causes neurological dysfunction, long-term disability, and death. Long-term increases in blood pressure can trigger stroke. Therefore, stroke prevention behavior needs to be improved as an effort to prevent stroke in hypertension patients. The purpose of this study is to represent stroke prevention behavior carried out by hypertension patients. The research design used is quantitative descriptive with a cross-sectional approach. The study was conducted in the working area of ​​the Sooko Community Health Center with a population of hypertension patients, the number of samples was 52 respondents with a sampling technique using purposive sampling. The results showed that most of the respondents carried out stroke prevention behavior in the adequate category as many as 27 respondents (52%). Stroke prevention behavior in the sufficient category can be reflected in the respondents' efforts to control blood pressure, take antihypertensive drugs as recommended, limit consumption of foods high in salt and fat, do regular exercise, and have regular health checks, although not yet done consistently.